PH Regulation by NHX-Type Antiporters Is Required for Receptor-Mediated Protein Trafficking to the Vacuole in Arabidopsis. Issue 4 (31st March 2015) - Reguera, Maria; Bassil, Elias; Tajima, Hiromi; Wimmer, Monika; Chanoca, Alexandra; Otegui, Marisa S.; Paris, Nadine; Blumwald, Eduardo
Abstract : Luminal pH of the Golgi, trans- Golgi network, and prevacuolar compartments is controlled by the Na + /H + antiporters NHX5 and NHX6 and required for protein processing and trafficking to vacuoles. Abstract: Protein trafficking requires proper ion and pH homeostasis of the endomembrane system. The NHX-type Na + /H + antiporters NHX5 and NHX6 localize to the Golgi, trans -Golgi network, and prevacuolar compartments and are required for growth and trafficking to the vacuole. In the nhx5 nhx6 T-DNA insertional knockouts, the precursors of the 2S albumin and 12S globulin storage proteins accumulated and were missorted to the apoplast. Immunoelectron microscopy revealed the presence of vesicle clusters containing storage protein precursors and vacuolar sorting receptors (VSRs). Isolation and identification of complexes of VSRs with unprocessed 12S globulin by 2D blue-native PAGE/SDS-PAGE indicated that the nhx5 nhx6 knockouts showed compromised receptor-cargo association. In vivo interaction studies using bimolecular fluorescence complementation between VSR2;1, aleurain, and 12S globulin suggested that nhx5 nhx6 knockouts showed a significant reduction of VSR binding to both cargoes. In vivo pH measurements indicated that the lumens of VSR compartments containing aleurain, as well as the trans -Golgi network and prevacuolar compartments, were significantly more acidic in nhx5 nhx6 knockouts. This work demonstrates the importance of NHX5 and NHX6 in maintaining endomembrane luminal pH and supports the notion that proper vacuolar trafficking and proteolytic processing of storage proteins require endomembrane pH homeostasis.